Methodological Considerations concerning the Assessment of Oral Competency in a Second Language (L2) - José González-Such; Jesús Jornet Meliá; Margarita Bakieva (Universidad Autónoma de Baja California, 2013)
In this paper we review methodological considerations about the assessment of oral proficiency in a second language. We discuss the characteristics of the construct and its definition, in this case with reference to proficiency, including competence in listening comprehension and oral expression. Also, we review concepts like how to design instruments and/or evaluative techniques for assessing the competencies that are involved, and considerations about reliability, validity and standard setting.